Zoledronic Acid Inhibits Human Osteoblast Activities - Basso, Fernanda G.; Silveira Turrioni, Ana Paula [UNESP]; Hebling, Josimeri [UNESP]; Souza Costa, Carlos A. de [UNESP] (Karger, 2013)
Background: Bisphosphonates are potent inhibitors of bone resorption. These kinds of drugs, which are used for the treatment of osteolytic diseases, have been associated with the occurrence of oral osteonecrosis, especially in patients over 60 years old. Current studies have demonstrated that the cytotoxic effects of bisphosphonates on osteoblasts play an important role in oral osteonecrosis development. Objective:The aim of this study was to evaluate the effect of long-term application of a highly potent bisphosphonate - zoledronic acid (ZA) - on human osteoblasts in vitro. Methods: Human osteoblasts (MG63 cell line) were seeded for 72 h in wells of 24-well plates. The Dulbecco's modified Eagle's medium (DMEM) was then replaced by culture medium without fetal bovine serum (FBS), and the cells were incubated for an additional 24 h, after which ZA was added to the DMEM without FBS and incubated in contact with osteoblasts for 7, 14 or 21 days. Cell viability (CV), total protein production (TPP), alkaline phosphatase (ALP) activity, mineral nodule formation (MNF), and gene expression of ALP and osteocalcin (OCN), as well as cell morphology by scanning electronic microscopy, were evaluated. Data were statistically analyzed by Kruskal-Wallis and Mann-Whitney tests, with a significance level of 5%. Results:The cytotoxic effects of ZA on osteoblasts were characterized by reduction of CV, TPP, ALP and MNF production. In addition, ZA MNF caused a decrease in gene expression of ALP and OCN, as well as intense cell morphology alterations. All these negative effects of ZA were concentration and period dependent. Conclusion: Both concentrations of ZA (1 and 5 mu m) caused cytotoxic effects to osteoblasts which reduced the production and expression of proteins that play an important role in bone matrix synthesis and mineralization. (C) 2013 S. Karger AG, Basel
Keywords: Bisphosphonates; Osteonecrosis; Osteoblasts; Cytotoxicity